2007
DOI: 10.1111/j.1440-1754.2007.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implementation of Integrated Management of Childhood Illness on improvement of health system in China

Abstract: The IMCI strategy has been shown to contribute to the improvement of the health system, promoting the efficient management of medical care at township and village level, as well as improving the relationship between doctors and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…[74][75][76][77][78][79][80][81][82][83]85 In low-income to medium-income countries, training of health-care workers as part of WHO's Integrated Management of Childhood Illness strategy has been shown to increase appropriate use of antimicrobials and decrease inappropriate use. [122][123][124][125] Non-physician health-care workers trained in integrated management of childhood illness might use antimicrobials more judiciously than physician providers. In resource-limited settings, training of nonphysician providers could increase both access to and appropriate use of antimicrobials; this is especially important in regions where inadequate numbers of physician providers could drive non-prescription antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…[74][75][76][77][78][79][80][81][82][83]85 In low-income to medium-income countries, training of health-care workers as part of WHO's Integrated Management of Childhood Illness strategy has been shown to increase appropriate use of antimicrobials and decrease inappropriate use. [122][123][124][125] Non-physician health-care workers trained in integrated management of childhood illness might use antimicrobials more judiciously than physician providers. In resource-limited settings, training of nonphysician providers could increase both access to and appropriate use of antimicrobials; this is especially important in regions where inadequate numbers of physician providers could drive non-prescription antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…China outperformed most of the 74 Countdown to 2015 countries (countries with high under-5 mortality rate, large numbers of under-5 deaths, or both) in its progress on major infectious causes, such as pneumonia and diarrhoea 25 . Improved socioeconomic status, water, sanitation, nutrition, and access to integrated management of childhood illness could be contributors to success 10, 26, 27. Major causes of neonatal mortality, such as preterm birth complications and intrapartum-related events, have also been steadily declining, which might be associated with increased quality of institutional delivery and neonatal resuscitation 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in South Africa found improvements in assessment of danger signs in sick children, rational prescribing, and initiation of treatment in the clinic following IMCI introduction [16]. In China, inappropriate prescription was shown to decrease from 44% to 3% for injection drugs, and from 60% to 6% for antibiotics after IMCI implementation [17]. In Morocco, correct prescription of antibiotics was also shown to significantly improve by nearly 30% [18].…”
Section: Morbidity Mortality and Health Service Quality Improvementsmentioning
confidence: 99%
“…One study in China found that availability of children's scales increased from 28% to 91%, timing devices from 89% to 97%, and utilities for mixing oral rehydration salts from 37% to 100% with the introduction of IMCI [17]. The same study also noted a significant increase in supply of all recommended drugs, vitamins, tetracycline eye ointment, and diazepam.…”
Section: Equipment and Suppliesmentioning
confidence: 99%